1996
DOI: 10.1074/jbc.271.36.21820
|View full text |Cite
|
Sign up to set email alerts
|

Quantitating Direct Chlorine Transfer from Enzyme to Substrate in Chloroperoxidase-catalyzed Reactions

Abstract: Substrate competition methods that were previously used to quantitate the involvement of free Cl 2 in the chloride-dependent peroxidatic reactions catalyzed by chloroperoxidase (CPO) (Libby, R. D., Shedd, A. L., Phipps, K. A., Beachy, T. M., and Gerstberger, S. M., (1992) J. Biol. Chem. 267, 1769 -1775) are extended to CPO-catalyzed halogenation reactions. Relative substrate specificities of halogen acceptor substrates (RHs) antipyrine (ap), NADH, 2-chlorodimedone (2cd), and barbituric acid (ba) are compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 23 publications
1
38
0
Order By: Relevance
“…One hypothesis is that CPO expresses a halogenating activity by the direct reaction of the intermediate with organic substrates. Several studies have shown that certain substrates are chlorinated at higher rates than others and much higher reaction rates are obtained with CPO when compared to the chlorination with HOCl (Dunford et al, 1987;Libby et al, 1996;Wagenknecht and Woggon, 1997;Murphy, 2003;Murali Manoj, 2006). These observations support the idea that the chlorination mechanism involved in the CPO catalyzed halogenation might be different from those of the non-enzymatic process.…”
Section: Heme-and Vanadate-dependent Haloperoxidases (Hpos)mentioning
confidence: 49%
“…One hypothesis is that CPO expresses a halogenating activity by the direct reaction of the intermediate with organic substrates. Several studies have shown that certain substrates are chlorinated at higher rates than others and much higher reaction rates are obtained with CPO when compared to the chlorination with HOCl (Dunford et al, 1987;Libby et al, 1996;Wagenknecht and Woggon, 1997;Murphy, 2003;Murali Manoj, 2006). These observations support the idea that the chlorination mechanism involved in the CPO catalyzed halogenation might be different from those of the non-enzymatic process.…”
Section: Heme-and Vanadate-dependent Haloperoxidases (Hpos)mentioning
confidence: 49%
“…cytochromes a, b, c and f) [1][2][3] which cycle between low-spin Fe(II) and low-spin Fe(III), small molecule binding and transport, 4,5 catalysis and O 2 activation (e.g. peroxidases and cytochromes P450) [6][7][8][9][10][11] where high valent Fe centers are involved in H atom abstraction, hydroxylation and epoxide formation. Heme sites are fundamentally different from non-heme iron sites in that the porphyrin ligand allows for the delocalization of the iron d electrons into the porphyrin π system.…”
Section: Introductionmentioning
confidence: 99%
“…Such a species has been detected spectroscopically at pH 4.4 (13). However, it has not yet been entirely resolved whether this hypohalite intermediate directly chlorinates the organic substrate (15), or if HOCl is released upon protonation of the intermediate, and free HOCl or Cl 2 perform the chlorination reactions (16). Because CPO shows only low substrate specificity and chlorinates a wide range of substrates non-stereospecifically (17), it might indeed be that free HOCl or Cl 2 perform these reactions in solution.…”
mentioning
confidence: 99%